Toward Multiplexed Optogenetic Circuits - Dwijayanti, Ari; Zhang, Congqiang; Poh, Chueh Loo; Lautier, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
Owing to its ubiquity and easy availability in Nature, light has been widely employed to control complex cellular behaviours. Light-sensitive proteins are the foundation to such diverse and multilevel adaptive regulations in a large range of organisms. Due to their remarkable properties and potential applications in engineered systems, exploration and engineering of natural light-sensitive proteins have significantly contributed to expand optogenetics toolboxes with tailor-made performances in synthetic chassis organisms. Progressively, more complex systems have been designed in which multiple photoreceptors, each sensing its dedicated wavelength, are combined to simultaneously coordinate cellular responses in a single cell. In this review, we highlight recent works and challenges on multiplexed optogenetics circuits in natural and engineered systems for dynamic regulation breakthrough in biotechnological applications.